2013
DOI: 10.1002/pssb.201349093
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of structural, elastic, electronic properties, and dispersion of optical functions of hexagonal ZnTiO3

Abstract: Structural, elastic, mechanical, electronic properties, and dispersion of optical functions of hexagonal ZnTiO3 have been investigated from first‐principles within density‐functional theory (DFT) using the norm‐conserving pseudopotentials method, within the generalized gradient approximation (GGA) to the exchange‐correlation functional. The calculated structural parameters agree with the available experimental and theoretical results. The elastic constants, bulk modulus, shear modulus, Young's modulus, Poisson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…Consequently, ZnTiO 3 has an energy bandgap quite similar to that of TiO 2 , due to the fact that ZnTiO 3 involves both ZnO and TiO 2 . Our calculated results agree with the literature [5,18,54].…”
Section: Optimization and Electronic Structure Of Zntio3 And Tio2supporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, ZnTiO 3 has an energy bandgap quite similar to that of TiO 2 , due to the fact that ZnTiO 3 involves both ZnO and TiO 2 . Our calculated results agree with the literature [5,18,54].…”
Section: Optimization and Electronic Structure Of Zntio3 And Tio2supporting
confidence: 91%
“…This ternary oxide has been widely used because of its outstanding properties and potential scientific and technical applications [17]. ZnTiO 3 has been investigated in a variety of applications as an antibacterial, catalyst, nanofiber, white pigment, microwave dielectric, gas sensor, nonlinear optical, corrosion inhibitor, and luminescent material [18][19][20][21][22][23], but its application in adsorption has not been sufficiently studied, despite the fact that the literature indicates that due to its great specific area, it could have an important potential as an adsorbent [24,25]. ZnTiO 3 is a polar oxide of the LiNbO 3 -type (LN-type) with both cations coordinated octahedrally in a three-dimensional framework of the octahedron perovskite (Pv) that shares corners [26].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that both the TiO 2 (anatase or rutile) and the ZnTiO 3 consist of a TiO 6 (and ZnO 6 for ZnTiO 3 ) octahedral structure unit. 26,27 In comparison with ZnTiO 3 , rutile possesses similar TiO 6 octahedra while the TiO 6 octahedra of anatase is much distorted. Because of the similar crystal structure unit, the occurrence of ZnTiO 3 on the surface of TiO 2 would induce the formation of rutile during the calcination progress.…”
Section: Discussionmentioning
confidence: 99%
“…It is found from Figure 3 that P-500 exhibits a typical anatase structure and only a small amount of rutile is observed. It is noted that the addition of [26][27] . To testify this, Zn doped TiO 2 with the addition of rutile is prepared by the same procedure as shown in Figure S4.…”
Section: Pagementioning
confidence: 99%
“…Zinc titanate ZnTiO 3 has been reported to have remarkable mechanical, optical and insulating properties [8,9]. Due to high photocatalytic activity it has caught high attention [10].…”
Section: Introductionmentioning
confidence: 99%